HISTOPATHOLOGICAL PATTERNS IN PAEDIATRIC IDIOPATHIC STEROID RESISTANT NEPHROTIC SYNDROME - Shah, Syed Sajid Hussain; Akhtar, Naureen; Sunbleen, Faiza; Rehman, Mohammad Fahim ur; Ahmed, Tausif (Journal of Ayub Medical College Abbottabad, 2015)
Background: Steroid-resistant nephrotic syndrome (SRNS) is a common problem but difficult to treat for pediatric nephrologists. Due to paucity of studies done in few centres in southern Pakistan regarding the histopathological aspects in paediatric patients with SRNS, this study was conducted to determine the histopathological spectrum in children with SRNS at our centre. Methods: This descriptive study has been conducted at the Nephrology department, The Children’s Hospital Lahore from February 2014 to January 2015. Based upon history, physical examination and laboratory results, all patients diagnosed as idiopathic SRNS were included in the study and renal biopsy was done to determine the underlying pathology. Histopathology reports were retrieved and data analysis done using SPSS-20.0. Results: There were a total of 96 patients, 64 (66.7%) males and 32 (33.3%) females. The age range was from 0.80 to 15 years with mean age of presentation being 6.34+3.75 years. The most common histo-pathological pattern was mesangio-proliferative Glomerulonephritis found in 79 (82.3%) cases followed by Focal segmental glomerulosclerosis (FSGS) in 9 (9.4%) patients while Minimal change disease (MCD) was seen in 5 (5.2%) subjects. Conclusion: Mesangioproliferative glomerulonephritis is the most common histological pattern seen in children presenting with idiopathic SRNS at our centre followed by FSGS and MCD